The genome sequence of the bluish flesh fly, Sarcophaga (Robineauella) caerulescens (Zetterstedt, 1838) [version 1; peer review: 2 approved] - Steven Falk; John F. Mulley (Wellcome Open Research, 2023)
We present a genome assembly from an individual male Sarcophaga caerulescens (the bluish flesh fly; Arthropoda; Insecta; Diptera; Sarcophagidae). The genome sequence is 597 megabases in span. Most of the assembly is scaffolded into seven chromosomal pseudomolecules, including the assembled X and Y sex chromosomes. The mitochondrial genome has also been assembled and is 21.1 kilobases in length. Gene annotation of this assembly on Ensembl identified 16,559 protein coding genes.